ROR2 is epigenetically inactivated in the early stages of colorectal neoplasia and is associated with proliferation and migration. Issue 1 (December 2016) - Ma, Sean; Srivastava, Sameer; Llamosas, Estelle; Hawkins, Nicholas; Hesson, Luke; Ward, Robyn; Ford, Caroline
Abstract Background Colorectal cancer (CRC) is closely linked to Wnt signalling, with 94 % of cases exhibiting a Wnt related mutation. ROR2 is a receptor tyrosine kinase that is thought to repress β-catenin dependent Wnt signalling. Our study aims to determine ifROR2 is epigenetically silenced in CRC and determine if in vitro silencing ofROR2 potentiates Wnt signalling, and alters the proliferative, migratory or invasive potential of cells. Methods ROR2 expression was examined in CRC cell lines and patient adenomas using qRT-PCR, while COBRA and bisulphite sequencing was used to analyseROR2 promoter methylation. 258 patient primary tumour samples from publicly available databases were also examined forROR2 expression and methylation. In addition, the functional effects ofROR2 modulation were investigated in HCT116 cells followingROR2 siRNA knockdown and in RKO and SW620 cells following ectopicROR2 expression. Results ReducedROR2 expression was found to correlate withROR2 promoter hypermethylation in colorectal cancer cell lines, carcinomas and adenomas.ROR2 expression was downregulated in 76.7 % (23/30) of CRC cell lines with increasingROR2 promoter hypermethylation correlating with progressively lower expression. Analysis of 239 primary tumour samples from a publicly available cohort also found a significant correlation between reducedROR2 expression and increased promoter methylation. Methylation analysis of 88 adenomas and 47 normal mucosa samples found greater percentage of adenoma samples to be methylated. Additional analysis also revealed that adenoma samples with reducedROR2 expression also possessedROR2 promoter hypermethylation.ROR2 knockdown in the CRC cell line HCT116 significantly decreased expression of the β-catenin independent Wnt targets genesJNK andNFATC1, increased cellular proliferation and migration but decreased invasion. WhenROR2 was ectopically expressed in RKO and SW620 cells, there was no significant change to either cellular proliferation or migration. Conclusion ROR2 is frequently epigenetically inactivated by promoter hypermethylation in the early stages of colorectal neoplasia and this may contribute to colorectal cancer progression by increasing cellular proliferation and migration.